Percutaneous Management of Malignant Biliary Strictures: Current Status and Future Directions - Attaya, Mohammed; Attaya, Hosam; Thabet, Ashraf (Digestive Disease Interventions, 2017)
Various minimally invasive percutaneous interventions may be performed for the treatment and management of malignant biliary obstruction. The types of percutaneous interventions include percutaneous transhepatic biliary drainage, percutaneous cholecystostomy, and biliary stent placement. Biliary stents have undergone continued evolution in design to prolong patency, increase cost-effectiveness, improve patient survival, and quality of life. Furthermore, investigational techniques, such as radiofrequency ablation, intraluminal brachytherapy, and photodynamic therapy promise new technologies in the field of biliary intervention. This review focuses on the current status of percutaneous therapies for malignant biliary strictures and obstruction.
Keywords: malignant biliary obstruction; percutaneous interventions; biliary drainage; biliary stents